(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Hastuti ED, Hastuti RB, Darmanti S. 2018. Plankton and benthos similarity indices as indicators of the impact of mangrove plantation on the environmental quality of silvofishery ponds. Biodiversitas 19: 1558-1567. This research was carried out in a coastal area of Semarang City, Central Java, Indonesia. It aimed to study the composition of plankton and benthos communities in silvofishery ponds, and to analyze the similarity in plankton and benthos composition between ponds as an indicator of variation in pond environmental quality. Nine pond treatments were sampled for their plankton and benthos composition. The nine treatments consisted of a factorial combination of three mangrove species assemblages (Avicennia marina (M1), Rhizophora mucronata (M2), and a mixture of both (M3)) at three mangrove populations (5 trees (S1), 10 trees (S2), and 15 trees (S3)). Similarity index analysis was conducted to measure the impact of treatments on the plankton and benthos communities. The total number of plankton species identified in observation periods in May, July and September of 2016, were 23, 16 and 21 species repectively, while for the benthos there were eight somewhat different species identified in each of the three observation periods. Fluctuation in plankton and benthos composition tended to achieve a balance in richness by the time of the the third observation period. Diatoms, particularly Gyrosigma sp., were the most widely distributed plankton in the first and third observation periods, while Pyramidella sulcata was the only well-distributed benthos species in the three observation periods. Pairwise similarity indices between treatments ranged from 0% to 62.5% for plankton and from 16.7% to 100% for benthos. The results of the investigation suggested that mangrove species affected plankton and benthos species richness in this initial stage of a silvofishery development: plankton composition appeared to be richer in ponds with A. marina, while benthos was richer in ponds with R. mucronata.